The influence of fiber alignment, structure and concentration on mechanical behavior of carbon nanofiber/epoxy composites: Experimental and numerical study. Issue 3 (30th November 2020) - Chanda, Amit; Sinha, Sujeet K; Datla, Naresh V
Abstract: The mechanical properties of epoxy‐based nanocomposites largely depend on fiber alignment, structure, concentration, and loading condition. To study the influence of these factors on the nonlinear stress‐strain behavior of epoxy nanocomposites, random and aligned carbon nanofiber (CNF)/epoxy composites were fabricated and tested under different strain rates. The elastic modulus and tensile strength were found to be increased as CNF concentrations increased for both random and transversely aligned nanocomposites. This behavior was accurately captured by a three‐dimensional representative volume element (RVE), where the fiber orientation and waviness were modeled from the experimental observation. This RVE predicted the increase in elastic modulus and tensile strength with increase in CNF concentration and strain rate as well as when the CNF alignment changes from transverse to longitudinal. Abstract : Mechanical properties of epoxy nanocomposites largely depend on fiber alignment, structure, concentration, and loading condition. To study the influence of these factors on the stress‐strain behavior of epoxy nanocomposites, random and aligned carbon nanofiber (CNF)/epoxy composites were fabricated and tested under different strain rates. The experimentally observed behavior and the effect of above‐mentioned factors were accurately captured in numerical modeling using a 3D representative volume element (RVE).